Costs and quality of life for prehabilitation and early rehabilitation after surgery of the lumbar spine - Andreasen Jakob; Asmussen Mikael; Nielsen Per Rotbøll; Tønnesen Hanne (BMC, 2008)
Abstract During the recent years improved operation techniques and administrative procedures have been developed for early rehabilitation. At the same time preoperative lifestyle intervention (prehabilitation) has revealed a large potential for additional risk reduction. The aim was to assess the quality of life and to estimate the cost-effectiveness of standard care versus an integrated programme including prehabilitation and early rehabilitation. Methods The analyses were based on the results from 60 patients undergoing lumbar fusion for degenerative lumbar disease; 28 patients were randomised to the integrated programme and 32 to the standard care programme. Data on cost and health related quality of life was collected preoperatively, during hospitalisation and postoperatively. The cost was estimated from multiplication of the resource consumption and price per unit. Results Overall there was no difference in health related quality of life scores. The patients from the integrated programme obtained their postoperative milestones sooner, returned to work and soaked less primary care after discharge. The integrated programme was 1,625€ (direct costs 494€ + indirect costs 1,131€) less costly per patient compared to the standard care programme. Conclusion The integrated programme of prehabilitation and early rehabilitation in spine surgery is more cost-effective compared to standard care programme alone.